Financing Difficulties of Small-and-Medium Enterprises In China - Yu, Jiali (2007)
China's economy reform and open-up policy has created an "enabling environment" for the development of small and medium enterprises (SMEs) in China especially with a great expansion of SMEs in private sectors. Nowadays, to some extent, SMEs have been the engine of the Chinese economic growth and the major contributor of the GDP. In the meantime, within this context of rapid SMEs development in China, the financing problems of SMEs have been the major impediment for the growth of SMEs in China. In this paper, I use a mixture of questionnaires and interviews in China with assistances of some secondary data from other surveys; through the study of current SMEs financing situation and SMEs financing policies, this paper will analyse the causes of this SMEs finance gab in China and put forward possible countermeasures to bridge such finance gab in SMEs financing.